Phytochemical screening and evaluation of antioxidant activities of Dracocephalum kotschyi and determination of its luteolin content - Mansureh Kamali; Susan Khosroyar; Hossein Kamali; Tooba Ahmadzadeh Sani; Ameneh Mohammadi (Avicenna Journal of Phytomedicine, 2016)
Objective: Dracocephalum kotschyi (Lamiaceae family) has been usedin traditional medicine for stomach and liver disorders, headache and congestion. In the present study, we have investigated phytochemical properties and antioxidant activities of dichloromethane, ethyl acetate and methanol extracts of D.kotschyi. Material and Methods: Antioxidant activities of extracts were evaluated using the integration of HPLC-DPPH and ferric reducing antioxidant power (FRAP) methods. In addition, the luteolincontent was determined using HPLC method. Results: The highest antioxidant activity was observed for the methanol extract (among the three tested extracts) showing 50% DPPH scavenging activity at 4.85µg/ml as compared to butylated hydroxy toluene (BHT) and ascorbic acid (3.00 µg/ml, 0.97 µg/ml). Also, luteolin was detected in methanol extract; it was identified by comparing its retention time and DAD spectra with standard and it was one of antioxidant components of this plant. In addition, the antioxidant activity of methanol extract was higher than BHT, in FRAP assay. Total phenolic content was in the range of 11.62-22.29 mg Gallic acid /gram of dry extract and flavonoid content was in the range of 3.97-5.042 mg             Quercetin/ gram of extract for dichloromethane, ethyl acetate and methanol extracts. The quantity of luteolin in D.kotschyiwas found to be 1061.005 µg/g of dried plant. Conclusion: The results of this investigation indicated that luteolin plays major role in the antioxidant activity of the plant.